Biografia do orvalho: Considerac¸ões sobre narrativa, vida e pesquisa em educac¸ão matemática - Santos Fernandes, Filipe [UNESP] (FapUNIFESP (SciELO), 2014)
In this paper, we seek to bring together three themes: narratives, lives, and researches in Mathematics Education. Taking into consideration the poetry from Manoel de Barros and a wide variety of contemporary authors, we emphasize - in terms of philosophy, methodology, and history - the enchantments and dangers of using life narratives, in its various forms, for researches in human sciences. In the end, we expect that the presented discussions will be an invitation to new ways of practicing research and, like a reverberation, the research in Mathematics Education.
Dew's biography: Preamble about narrative, life and mathematics education research
Keywords: Biography; Mathematics education; Narrative; Research